Clay and Clay Minerals: A Detailed Review - Belghazdis, Mohammed; Hachem, El-Kaber (International Journal of Recent Technology and Applied Science (IJORTAS), 2022)
In this study, we focused on the presentation of clay minerals, their conditions of formation and their different categories. We also reported the importance of purification in removing impurities and the responses induced by heat treatment of these minerals. Techniques used to detect clay minerals are also exposed. On the other hand, the mineralogical, physicochemical and thermal properties have a direct impact on the field of use of these minerals. These properties differ from one mineral to another, depending on the structure and chemical composition. Moreover, the remarkable properties of smectites make these minerals the most preferred for the industry and also in the environmental field. Due to their brilliant firing properties, illites are suitable for the construction industry. Moreover, the purification by acids (acetic acid and HCl) allows the removal of most associated minerals, and thus a secure access to the clays' characteristics and a very strong sensitization even to the small variation. Finally, the ethylene glycol (EG) swelling test only affects the basal distance of smectites, increasing this distance to 17 Å, but heating to 500°C destroys kaolinite, and closes the basal distance of smectites and vermiculites to 10 Å. Illites and chlorites show no response to these two treatments (EG, heating to 500°C).